Teaching creatively and teaching for creativity: distinctions and relationships - Jeffrey, Bob; Craft, Anna (Educational studies, 2004)
The distinction and relationship between teaching creatively and teaching for creativity identified in the report from the National Advisory Committee on Creative and Cultural Education ( NACCCE, 1999), is examined by focusing on empirical research from an early years school, known for its creative approach. The examination uses four characteristics of creativity and pedagogy identified by Peter Woods (1990): relevance, ownership, control and innovation, to show the interdependence of the NACCCE distinctions. We conclude that although the NACCCE distinction between teaching creatively and teaching for creativity has been useful as an analytical tool, it may, at the same time, have dichotomised an integrated practice and we suggest that a more useful distinction for the study of creative pedagogies would be the relationship between teaching creatively and creative learning.